Factors Affecting the Production of the Coffee Farming in Uluway Village Mengkendek Sub District Tana Toraja District - Mersi, Renatha; Padangaran, Ayub Manggala; Sadimantara, Fahria Nadiryati (Department of Agribusiness, Halu Oleo University, 2021)
This study aimed to determine what factors influence coffee production in Uluway Village, Mengkendek Sub District of Tana Toraja District. The research was conducted from March to May 2020 where these factors include land area, labor, fertilizers, and pesticides. This study aimed to determine what factors influence the people's coffee production in Uluway Village, Mengkendek Sub District of Tana Toraja District. The population of this study was all the farmers who cultivated coffee in Uluway Village, Mengkendek Sub District of Tana Toraja District. The sample of this study was 78 respondents who were determined by using the census method. The analytical method used is descriptive qualitative data analysis, the second data analysis using multiple linear regression analysis, and the third. The research results can be drawn from several conclusions, including the coffee farming processing techniques in Uluway Village, namely land preparation, planting, maintenance, harvesting, and postharvest. Factors that have a real effect include land area, fertilizers, and pesticides, while factors that do not affect coffee production are labor